Comparison of soil fertility levels of coffee-based agroforestry land cultivation types based on the QBS-ar soil microarthropod index - Psn Masruri Sulistiyanto Ari; Rully Rahadian; Mochamad Hadi (DIVERSITAS HAYATI, 2023)
Coffee-based agroforestry is a method for dealing with the conversion of forest land into plantations which is considered safe in reducing levels of surface runoff and erosion. This reduction results in lower leaching of trace elements which results in the soil maintaining its fertility. This study aims to evaluate soil fertility in two types of land management in the Ungaran Mountain agroforestry area, Semarang using the QBS-ar soil microarthropod index. Sampling was done in two coffee agroforestry land management types, including Intensive Semirang; Non-Intensive- Gonoharjo. QBS-ar is carried out by taking soil samples, installing a pitfall trap, and extracting using the Tullgren-Funnel method. Microarthropods from sampling results were identified to order level. The soil physical and chemical factors measured are pH, organic matter, soil moisture, and soil temperature. Biological soil quality was analyzed using the procedure for determining the Eco-Morphological Index (EMI) and QBS-ar index values. The research results show that the QBS-ar index value for the Non-Intensive land type (46) has a high level of fertility compared to the Intensive land type (23). The soil organic matter value is intensive (14.4) and non-intensive (17.8) with soil pH values in the three locations ranging from 5.8–6.4.